The sharing economy and the antecedents of resource sharing intentions: Evidence from a developing country - Mark Ratilla (Taylor & Francis Group, 2021)
As the sharing economy continues to diffuse in the global sphere, this paper seeks to understand the relevant behavioral antecedents for individuals to supply resources in technology-enabled platforms, especially in environments where resource scarcity subsists and the cultural landscape varies. Explicitly, we examine the impact of a set of belief factors and the individual-level collectivistic orientation on the core constructs of the Theory of Planned Behavior. A web-based survey was carried out in the Philippines, and a total of 365 valid responses were analyzed using partial least squares structural equation modeling. Results show that attitude and perceived behavioral control strongly drive the consumers’ intention to share resources in the sharing economy. Attitude is markedly preceded by altruistic and social tenets traditionally attached to sharing practices, while perceived behavioral control is endorsed by perceived trust and ease of use. Also, this work recognizes the attributions of culture to behavior as evidenced by the significant positive effect of collectivism towards the subjective norm. However, the potency of subjective norms on behavioral intention is argued. The study findings offer relevant insights to existing and prospective sharing economy platform providers in fostering peer-provider participation in the less developed world.